The role of mothers’ facial expressions of emotions in infants’ language competence - Goh, Kimberly Jia Yen (Nanyang Technological University, 2020)
The role of language in facial expressions of emotions (FEE) has been demonstrated in empirical studies (Widen, 2013) but evidence on the role that FEE plays in language competence is surprisingly scarce, despite the benefits of FEE in social, cognitive and emotional development. This study is the first to examine the role of mothers’ six basic FEE (anger, disgust, happiness, fear, sadness and surprise) in younger (10- to 12-month-old) and older (15- to 18-month-old) infants’ receptive and expressive language competence. 32 mothers were rated for their level and intensity of FEE using the Emotion Facial Action Coding System. Their infants were tested for their language competence using The Bayley Scales of Infant and Toddler Development Language Scale subtest. Pearson correlation and simple linear regression analysis revealed four significant correlations: 1) mothers’ level of sad FEE and younger infants’ expressive language, 2) mothers’ intensity of sad FEE and younger infants’ expressive language and 3) mothers’ intensity of fearful FEE and older infants’ receptive language and 4) mothers’ intensity of surprise FEE and younger infants’ expressive language. The findings shed critical light on particular FEE that predict infants’ language competence. The conclusion from the findings posit that the purpose of mothers’ FEE in infants’ lives, instead of infants’ attention bias towards negative-valence FEE is correlated to infants’ language competence.